Phenomenological Study of Lived Experiences of International Students in Turkey - Kılınç, Ali C; Arslan, Kürşat; Polat, Mustafa (Journal of International Students, 2020)
Internationalization trends in higher education have become a significantly accentuated issue and student mobility is considered as one of the core components of internationalization in higher education. This study focuses on investigating the lived experiences of international students at a state university in Turkey using qualitative research method and phenomenological design. The research data were collected through semi-structured interviews in order to reveal the participants’ experiences and their overall insight into studying abroad. 10 international students from various countries in accordance with the maximum variation sampling technique participated in the current study. The findings provide a rich description of the lived experiences of international students regarding their perceptions of studying abroad. Results of the data analysis yielded two major themes entitled “Perceptions of being an international student: What does it mean? What have they experienced?” and “The assistance and challenges they have been through during their study”.